If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3h + 4 = 8h Reorder the terms: 4 + 3h = 8h Solving 4 + 3h = 8h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-8h' to each side of the equation. 4 + 3h + -8h = 8h + -8h Combine like terms: 3h + -8h = -5h 4 + -5h = 8h + -8h Combine like terms: 8h + -8h = 0 4 + -5h = 0 Add '-4' to each side of the equation. 4 + -4 + -5h = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -5h = 0 + -4 -5h = 0 + -4 Combine like terms: 0 + -4 = -4 -5h = -4 Divide each side by '-5'. h = 0.8 Simplifying h = 0.8
| xm=npsolvex | | 117x-9(x+4)=3x-26 | | cos(x)-0.8x^2=0 | | -x^2+8x=10 | | Lgx=-3 | | -10x+9=12 | | 6x+4=6x+20 | | 10x^4-21x^2+4=0 | | Sen2x=2/2 | | 60=x^2 | | 4(f+5)=120 | | -6(x+3)-2=-38 | | 3(-4)+2y=-11 | | 25=1+3u | | 2(3-5x)+8x=-35 | | -20=16y | | x^2-11x+19=(-5) | | z^2=12+16i | | 5(x-5/)=4(x-3/4) | | 4(s+2)-4= | | 3(x-8)=-54 | | X+(x+2)+3=(x+1)+50 | | 3x(-3)=36 | | 2x-6=x+24 | | 2(-2y+3)=26 | | 3(-5)-2y=-11 | | 10+11x=-12 | | 4b-9b=-35 | | 2(x-2)-6=2 | | 4(3)-6y=-18 | | 3a+12=6a-8-5a | | 9(2)-5y=-2 |